New Mexico Marriages, Union County Volume 1 1893-1940 - Lofgreen, June.; Windham, Margaret Leonard (Albuquerque, NM New Mexico Genealogical Society, 1994)
Marriages registered in Union County from 1893 - 1940
89351
Keywords: Marriage records -- Union County (N.M.); Genealogy -- Union County (N.M.); Vital records -- Union County (N.M.)